Synchrotron radiation-based Fourier-transform infrared spectromicroscopy for characterization of the protein/peptide distribution in single microspheres - Manli Wang; Xiaolong Lu; Xianzhen Yin; Yajun Tong; Weiwei Peng; Li Wu; Haiyan Li; Yan Yang; Jingkai Gu; Tiqiao Xiao; Min Chen; Jiwen Zhang (Elsevier, 2015)
The present study establishes a visualization method for the measurement of the distribution and localization of protein/peptide constituents within a single poly-lactide-co-glycolide (PLGA) microsphere using synchrotron radiation-based Fourier-transform infrared spectromicroscopy (SR-FTIR). The representative infrared wavenumbers specific for protein/peptide (Exenatide) and excipient (PLGA) were identified and chemical maps at the single microsphere level were generated by measuring and plotting the intensity of these specific bands. For quantitative analysis of the distribution within microspheres, Matlab software was used to transform the map file into a 3D matrix and the matrix values specific for the drug and excipient were extracted. Comparison of the normalized SR-FTIR maps of PLGA and Exenatide indicated that PLGA was uniformly distributed, while Exenatide was relatively non-uniformly distributed in the microspheres. In conclusion, SR-FTIR is a rapid, nondestructive and sensitive detection technology to provide the distribution of chemical constituents and functional groups in microparticles and microspheres.